An experimental study on the effect of gas injection configuration on flow characteristics in high viscosity oil columns. (19th October 2021) - Mohammed, Shara K.; Hasan, Abbas H.; Ibrahim, Abubakr; Dimitrakis, Georgios
Abstract: Gas‐viscous liquid bubbly and slug flow are very common in petroleum, chemical, bioengineering, polymer, and food processing. However, there is a major knowledge gap in two‐phase flow research in the design of gas injectors/distributers in very high viscosity oil systems. The present study investigates the effect of gas injection methods in columns containing very high viscosity oils (i.e., realistic liquids), and more specifically using 360 Pa · s viscosity oil in a 240‐mm diameter column. The effects that the radial positioning, number of gas nozzles, and their distance from each other have on the structure of the flow in viscous liquids are presented in detail. Electrical capacitance tomography (ECT) is used to extract experimental data. Void fraction, bubble velocity, frequency, liquid film thickness, and bubble length were measured and analyzed at different radial gas injection positions. It has been observed that bubble length increases significantly by 0.3 m when the injection nozzle is located next to the wall of the pipe. Bubble velocity and length also increase by 0.217 m/s and 3.6 m, respectively, with increasing gas flowrate when multiple injection points are used. Increasing the distance between the gas injection points increased bubbles' length by 1.2 m. Bubbles' velocity and frequency (at higher gas flow rate) were also increased.